Action of philanthotoxin on ion channels of arthropod muscle - Khan, Tanwir Rahman (1994)
Calcium ions play an important role in many signalling pathways involved in normal cell metabolism. Pertrebations of normal Ca++ signalling may also play a pivotal role in the initiation of cell death. In these studies I have examined the influx of 45Ca++ into the extensor tibiae muscle of the locust (Schistocerca gregaria ). 45Ca++ entry could be stimulated by the addition of glutamate receptor-agonists or by activation of voltage activated calcium channels. L-glutamate, L-quisqualate and NMDA stimulated the influx of 45Ca++ while L-aspartate had only a small effect. DL-ibotenate, kainate, AMPA and glycine had no effect on 45Ca++ uptake (all agonists were tested at concentrations up to (100μM). Glycine (1μM) enhanced the 45Ca++ entry induced by NMDA and L-glutamate. Only the glycine potentiation of L-glu-stimulated responses was abolished in the presence of Mg++ (2mM) or AP5 (10μM) whereas the NMDA-stimulated response was completely abolished by these agents. These finding suggests that in the presence of glycine, L-glutamate may activate NMDA receptors and that in the absence of glycine L-glu-stimulated 45Ca++ entry occurs via activation of the qGluR. Depolarisation of the extensor tibiae muscles (50mM KCl) stimulated 45Ca++ influx by activation of voltage-sensitive calcium channels. Philanthotoxin-343 (0.1μM) had no effect on depolarisation activated calcium entry, however, nifedipine (1μM) an L-type calcium channel antagonist inhibited this Ca++ influx. Nifedipine did not inhibit L-glu-stimulated Ca++ entry suggesting that in these muscles L-type Ca++ channels are not involved in the Ca++ influx pathway following G1uR activation. Philanthotoxin-433 (PhTX-433) and many of its synthetic analogues are potent inhibitors of locust GluR. In the future these analogues may prove as useful potential neuroprotective agents or as novel pesticides. Over 100 analogues of PhTX-433 have been synthesized with changes made in the four regions of the structure, the thermospermine moiety, the tyrosyl moiety, the butyryl moiety and the terminal amino moiety. The effects of different concentrations (10-4M to 10-14M) of synthetic analogues of PhTX-433 (PhTX-343, PhTX-343-Arg, PhTX-4) were investigated in the 45Ca++ influx assay using locust extensor tibiae muscle. PhTX-343-Arg was more potent (IC50= - 7x10-9) than PhTX- 343 (IC50= - 10-8M) or PhTX-4 in blocking 45Ca H uptake. These findings were further supported by electrophysiological studies. The interaction of these synthetic analogues of philanthotoxin with GluR of locust muscle were further investigated by examining the effect of these compounds on evoked excitatory post synaptic potentials. In recent years control of ticks have been very important issue because of the social and economical damage they cause. Neuromuscular transmission is a main target site for the chemical control of many pests. Philanthotoxin and its analogues block the glutamate receptors which are involved in arthropod neuromuscular transmission and thus may prove useful as novel pesticides. The action of synthetic analogues of philanthotoxin (C7PhTX-343, DNP12-, PhTX-343 and PhTX-343) were examined on evoked excitatory postsynaptic potential in tick coxal muscle. These compounds all antagonized the evoked EPSP. C7PhTX-343 and DNP12-PhTX-343 exhibited same potency (IC50 = 10-8M) and both were more potent than PhTX-343 (IC50 ='2X10-5M). In recent years Xenopus oocyte has taken over a new role as a test tube for the study of the biogenesis, functional architecture and modulation of plasma membrane protein. Attempts were made to express mRNA from embryonic tissue of tick and locust leg muscle in to Xenopus oocyte for pharmacological studies. Xenopus oocytes failed to translate RNA faithfully and efficiently from these sources. Rat brain RNA injected oocytes used as control, expressed routinely.